Development of a Prototype Embedded 3D Printer with Dual Ink-Gel Extrusion Capability - Van Driel, A.; Govender, R.A. (The South African Journal of Industrial Engineering, 2025)
3D printing has advanced significantly, enabling new applications such as embedded 3D printing for materials that solidify slowly. This method prints liquid materials into a support gel that holds their shape while curing. This project developed the dual ink-gel extruder (DIGEX) to address the limitations in the print volume seen in previous projects and to enable the simultaneous extrusion of material and support gel. Various sub-assemblies and deposition techniques were tested to optimise performance. While DIGEX successfully demonstrated the concept, difficulties remain in scaling for large-format printing, requiring further refinement in hardware, software, and process configurations.